Irregolarità e impedimenti: vie di conoscenza e di verifica al servizio del discernimento - Migliavacca, Andrea (Quaderni di diritto ecclesiale, 2015)
The institute of irregularities and impediments for the reception or exercise of Holy Orders is a question that elicits an evaluation and a discovery of which paths of understanding exist in such situations during the formation years of seminarians. Same Circular Letters by the Congregation for Catholic Education in 1992 and in 1999 invited local Ordinaries to take care that a complete and insightful information on this theme be given to seminarians during their first years of formation, in order to allow them to have an understanding of this institute and to evaluate in time any situations that come up. The issue raises also the theme of responsibiHty of the various active elements information, the entire Christian community and particularly candidates to Holy Orders. Same instruments and useful considerations for understanding are identified: the Commission for Admission to Holy Orders, Verifications, documentation, the use of digital information and the use of information coming through expert advice, particularry from psychology. The reflection highlights the contemporaneity of the theme of verification and discernment during formation to Sacred Ministry.